2014
DOI: 10.1159/000367653
|View full text |Cite
|
Sign up to set email alerts
|

Health, Social and Economic Consequences of Polyneuropathy: A Controlled National Study Evaluating Societal Effects on Patients and Their Partners

Abstract: Objectives: To estimate the direct and indirect factual costs of polyneuropathy in a national sample of patients and their spouses based on a national register-based cohort study with matched controls. Methods: Using records from the Danish National Patient Registry (1997-2009) all patients with a diagnosis of polyneuropathy and their partners were identified and compared with randomly chosen controls matched for age, gender, geographic area and civil status. Direct costs included frequencies of primary and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Due to the large number of people with epilepsy, and the early onset of the disorder [10,11], the total societal burden is significant. Generally, disorders of the brain cause a substantial societal burden [31][32][33] due to the involvement of comorbidities but also social costs [34]. However, it is difficult to obtain a balanced cost estimate between diseases due to differences in mortality rates, comorbidities, age and gender effects and compare effect between heterogeneous disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large number of people with epilepsy, and the early onset of the disorder [10,11], the total societal burden is significant. Generally, disorders of the brain cause a substantial societal burden [31][32][33] due to the involvement of comorbidities but also social costs [34]. However, it is difficult to obtain a balanced cost estimate between diseases due to differences in mortality rates, comorbidities, age and gender effects and compare effect between heterogeneous disorders.…”
Section: Discussionmentioning
confidence: 99%
“…3 Spinal mobilizations-low velocity passive oscillatory movements 4 -are widely used by physical therapists in spinal pain management [5][6][7] and are recommended by clinical guidelines. [8][9][10] Effects are moderate, [11][12][13] however, outcomes are improved when application is based on patient classification.…”
mentioning
confidence: 99%
“…1 Studies have shown that HNIs have resulted in deteriorated marital relationships, decreased income, and a feeling of loneliness resulting from a lack of social interaction. 10,21…”
Section: Discussionmentioning
confidence: 99%